(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The artistic subject includes relationships derived from the social fabric as the artist is an important part of society and his ability to express and influence society through an aesthetic discourse within a dialogue outside the traditional meaning. From this, the focus has been on the intellectual connotations of the mother-child duality, as the forms carry intellectual implications. Through which the aesthetic meaning is highlighted, the current research was concerned with studying ((the intellectual implications of the duality of mother and child in contemporary sculpture), and it included four chapters. The first chapter presents the research problem, which centered on the following question: What is the nature of the intellectual messages of the mother-child duality in contemporary sculpture